2019
DOI: 10.1002/tal.1687
|View full text |Cite
|
Sign up to set email alerts
|

Seismic collapse risk assessment of super high‐rise buildings considering modeling uncertainty: A case study

Abstract: Based on the multiple stripes analysis method and the first-order second-moment method, a seismic collapse risk assessment considering the modeling uncertainty is carried out for a 118-story super high-rise building with a typical mega-frame/coretube/outrigger resisting system. The sensitivity of the median collapse capacity of the building to eight main parameters is analyzed, and then the modeling uncertainty is determined. Both the effects of the characterization methods of bidirectional ground motion inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Thirty pairs of far-field ground motions (see Table 3) are selected here from the PEER strong motion database [42][43][44] according to the selection criteria recommended in FEMA P695 [45]. The source-to-distance of the far-field ground motions is greater than 10 km, and enough records from large-magnitude earthquake events are chosen to ensure record-to-record variability.…”
Section: Selection Of Ground Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty pairs of far-field ground motions (see Table 3) are selected here from the PEER strong motion database [42][43][44] according to the selection criteria recommended in FEMA P695 [45]. The source-to-distance of the far-field ground motions is greater than 10 km, and enough records from large-magnitude earthquake events are chosen to ensure record-to-record variability.…”
Section: Selection Of Ground Motionsmentioning
confidence: 99%
“…Héctor Dávalos et al [48] recommended that it is better to conduct multiple stripes analyses at only two intensity levels, namely, enhanced two-stripe analysis (E2SA). Zhang et al [44] suggested using three IM levels with two levels lower than the estimated median limit capacity in the multiple stripes analysis. In general, an accurate result can be obtained by the IM levels focused on the lower half of the fragility curve.…”
Section: Multiple Stripes Analysis and Criteria For Each Damage Limit Statementioning
confidence: 99%